Gerakan Silicon Valley Indian Professionals Association (SIPA) Dalam Membantu India Mengubah Brain Drain Menjadi Brain Circulation - Rika Isnarti (Department of International Relations, Universitas Andalas)
India has a lot of skilled IT workers and most of them migrate to US. In migration studies, this situation is called brain drain. Migration of skilled workers from developing countries to developed countries. This research tries to analyze the movement of an Indian IT diaspora network in U.S, the Silicon Valley Indian Professionals Association (SIPA),which is trying to help India to reduce the impact of brain drain and to create brain circulation.This research is a library research and uses neogramscian framework.This research concluded that brain drain is one of commodification on skilled term. Today, commodification is not only for raw materials, but also skills. This situation faces by skilled labour when they migrate to developed countries and used to support the privillege of developed country. SIPA as Indian diaspora success to create brain circulation for India. SIPA seeks to transform the workers to work in India from early worked in the US, by increasing workers' technical knowledge, entrepreneurship, and understanding migrant contribution for home country or to India. Besides, SIPA also seeks to cooperate with Indian government created a comparative advantage for the IT industry in India.